Manajemen Kepemimpinan Kepala Sekolah Sebagai Administrator Dalam Peningkatan Kompetensi Guru - Roza Andria Lova; Iswantir M (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research discusses the principal's leadership management in improving teachers' competencies at SD Lebah Pembelajar, Bukittinggi. The principal as the main administrator in the school has an important role in ensuring effective education delivery. The data collection methods used were observation, interview and documentation. Furthermore, the data were analysed qualitatively by means of data reduction, data presentation and verification and conclusion drawing. The findings show that only a handful of principals are qualified in school management and there are still mistakes in carrying out the role of administrator. Several factors such as human resources and the perception that the principal is everything in the school become obstacles in the implementation of leadership tasks. The principal's strategy in SD Lebah Pembelajar in improving teachers' competence, starting from policy formulation, organising work procedures, to supervising the learning process, became the focus of the research. The results show that the principal's management plays an important role in improving teachers' competence. Moral and material support, policy formulation, work organisation and effective supervision are key factors in achieving the goal of improving the quality of education at SD Lebah Pembelajar. This research provides important insights for formulating relevant adaptation and mitigation policies at the school level.